2018
DOI: 10.1002/tafs.10101
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Contemporary Gene Flow and the Genetic Structure of Muskellunge in the Ohio River Drainage

Abstract: Muskellunge Esox masquinongy is a recreationally important species distributed throughout the Ohio, upper Mississippi, and Great Lakes drainages and has been introduced outside of its native range. We conducted a survey of microsatellite DNA variation among 11 populations, natural, managed, and hatchery, in the Ohio River drainage. Microsatellite DNA variation was highly significant among all populations. A CLUSTER analysis identified K = 2 populations corresponding to populations east and west of the Ohio Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Low survival and/or reproductive success of stocked fish has been reported mostly in salmonid species characterized by putatively high rate of local adaptation (Araki, Cooper, & Blouin, ; Araki et al, ; Araki & Schmid, ; Christie, Ford, & Blouin, ; Thériault, Moyer, & Banks, ; Thériault, Moyer, Jackson, Blouin, & Banks, ). Similarly, in Muskellunge, low levels of admixture from the same Ohio strain used in our study, was observed following intensive stocking into West Virginia streams despite their high use (White, Kohli, & Converse, ). Our results do not necessarily invoke a mechanism of negative selection or lower fitness of individuals to explain observed pattern.…”
Section: Discussionsupporting
confidence: 69%
“…Low survival and/or reproductive success of stocked fish has been reported mostly in salmonid species characterized by putatively high rate of local adaptation (Araki, Cooper, & Blouin, ; Araki et al, ; Araki & Schmid, ; Christie, Ford, & Blouin, ; Thériault, Moyer, & Banks, ; Thériault, Moyer, Jackson, Blouin, & Banks, ). Similarly, in Muskellunge, low levels of admixture from the same Ohio strain used in our study, was observed following intensive stocking into West Virginia streams despite their high use (White, Kohli, & Converse, ). Our results do not necessarily invoke a mechanism of negative selection or lower fitness of individuals to explain observed pattern.…”
Section: Discussionsupporting
confidence: 69%